Cobalt–nickel material libraries obtained from electrodeposition using citrate or glycine as additives. Issue 6 (16th February 2016) - Grill, Carina Daniela; Pötzelberger, Isabella; Kollender, Jan Philipp; Hassel, Achim Walter
Abstract: Abstractauthoren Fabrication of cobalt–nickel material libraries was performed by electrodeposition in a modified 3D‐printed Hull cell using sulfate‐based electrolyte baths containing trisodium citrate or glycine as additives. A transition from anomalous to normal co‐deposition behavior was observed for different overall applied current densities. Scanning electron microscopy (SEM) images showed needle‐shaped crystallites on the sample obtained from citrate solution and a nodular surface morphology for the material library from glycine solution. Non‐enzymatic glucose sensing was carried out by flow‐type scanning droplet cell microscopy (FT‐SDCM) to investigate the electrocatalytic activity for glucose oxidation. Cobalt–nickel material library fabricated by electrodeposition in the presence of trisodium citrate or glycine as additives using a modified 3D‐printed Hull cell.